THE MANIFESTATION OF NATIONAL IDENTITY IN THE WORKS BY TARAS SHEVCHENKO AND ROBERT BURNS - Martynets, A. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
This article analyzes the works of T. Shevchenko and R. Burns through the prism of their appeal to the historical past and finding there the support for the formation of the national consciousness of the authors.